Mapping women's empowerment : experiences from Bangladesh, India, and Pakistan - Pathways of Women's Empowerment Programme. South Asia Hub. Scoping Workshop (2006 : Dhaka, Bangladesh); Azim, Firdous, 1952-; Sultan, Maheen; BRAC University (Dhaka : University Press Limited, 2010)
Papers presented at the Scoping Workshop of the South Asia Hub of the Women's Empowerment Programme sponsored by BRAC University, held from August 18-21, 2006 in Dhaka.
"BRAC Development Institute."
Includes bibliographical references and index.
Keywords: Women in development -- Bangladesh -- Congresses; Women in development -- India -- Congresses; Women in development -- Pakistan -- Congresses; Women -- Political activity -- Bangladesh -- Congresses; Women -- Political activity -- India -- Congresses; Women -- Political activity -- Pakistan -- Congresses